Pengaruh Leverage, Risiko Perusahaan Dan Kepemilikan Institusional Terhadap Tindakan Penghindaran Pajak (Studi Empiris pada Perusahaan Manufaktur Sektor Logam yang Terdaftar BEI Tahun 2014-2018) - Romadona, Rahadian; Setiyorini, Wahyu (-)
This study aims to analyze and obtain empirical evidence about the effect of leverage, company risk, and institutional ownership on tax avoidance. The sample of this research is the metal sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The number of samples in this study were 18 companies with 5-year observations obtained by the purposive sampling method. The method of analysis of this research uses the Multiple Regression Model. The results of this study indicate that leverage, company risk and institutional ownership significantly influence tax avoidance. Keywords: Leverage, company risk, institutional ownership, Tax avoidance.